HEAD NURSES’ LEADERSHIP STYLES AND THEIR IMPACT ON STAFF INPATIENT NURSES’ JOB PERFORMANCE: AN INTEGRATIVE REVIEW - Hamonangan Tambunan; Evelyn Hemme Tambunan (Universitas Kadiri, 2025)
This integrative review aims to examines how head nurses' leadership styles impact quantifiable job performance metrics of staff inpatient nurses who work in acute care hospital settings. This research review synthesizes quantitative studies from peer-reviewed nursing journals over the past 10 years. We utilized databases CINAHL, PubMed, and Scopus to locate studies that incorporate standardized quantitative metrics and critical appraisal tools for assessing leadership effectiveness. The research team used a PRISMA flow diagram to maintain transparency throughout the process of literature selection. Transformative leadership shows the strongest positive correlation with nurse job performance outcomes such as increased patient satisfaction ratings alongside reduced staff turnover and improved clinical skills. The research field exhibits notable gaps because study designs vary widely while performance metrics and longitudinal data remain insufficient. Future research should employ strong methodological frameworks to further clarify how specific leadership behaviors affect staff outcomes. Nurse managers and policy makers should focus on creating leadership development programs and organizational approaches that optimize staff performance within acute care settings.